Analysis of Jurisprudential Works of Abul Barakat Nasafi - Baymirov Muslim Saidullaevich (Researchparks Publishing, 2023)
In this article, Abul Barakat Nasafi, based on the principle of tolerance of the Hanafi madhhab, finds answers to social, religious and ideological questions, relying on the sources of the Shariah, brings to people the divine meanings in their purest form, striving always to call mankind to unity, harmony and peace, and allama was created as a result of the Mongol invasion. He has made a great contribution to the development of science in the region with his mature knowledge and invaluable works in the fields of tafsir, fiqh and aqeedah. It is emphasised that the issues described and analysed in the works of the scholar are still of great importance today.